Decision support system to determine the best customer using weighted aggregated sum product assessment method - Saifur Rohman Cholil; Andri Roy Irawan (Jurnal Teknik Informatika C.I.T Medicom, 2023)
A business engaged in the sale of building materials and building tools. Customers are important assets that must be maintained properly, because each customer will bring profits that can keep the business running. To maintain customer loyalty, business owners provide an appreciation and appreciation for the best customers. However, determining the best customer is still difficult because the process of determining the best customer is still done manually and randomly. The number of customers is also an obstacle to the process of determining the best customer. The method used is weighted aggregated sum product assessment (WASPAS) to determine the best customer by looking at 5 criteria including: Total Spend, Visit Loyalty, Quantity of Shopping, Distance, Frequency of Complaints. This method was chosen because it can reduce errors - errors or optimize in estimation for the selection of the highest and lowest values. The best customers will be rewarded and appreciated by business owners.Â  The result of this study is a Decision Support System to Determine the Best Customer Using the WASPAS Method. Questionnaire testing obtained user satisfaction results as much as 65% strongly agree, 25% agree, 10% sufficient and 0% disagree which shows that the system is in accordance with the needs and can be used.